The Influence of Teacher Professionalism Development of Youth Capacity Improvement in Deli Serdang - Lubis, Khairuddin; Lubis, Suwardi; Rujiman (TALENTA Publisher, Universitas Sumatera Utara, 2020)
Teachers have a strategic role in education. Other educational resources become less significant if not accompanied by quality teachers. Teacher plays a key role to advanced education in the withdrawal of an educational unit. Teachers are the spearhead in the effort to improve service quality and educational outcomes. The purpose of this study is to analyze the availability of Senior High School teacher to improve youth capacity. This research was conducted at three of State Senior High School in Deli Serdang regency sample of 53 teachers. Variable research is the development of teacher professionalism as an independent variable and the improvement of youth capacity as a variable bound. Data collection using questionnaires, documentation, interviews and observation. Data were analyzed descriptively and using simple linear regression analysis. Teacher professionalism has a significant effect on youth capacity in Deli Serdang Regency.